THE MEDIATING EFFECTS OF ESL STUDENTS’ LEARNING STYLES IN THE RELATIONSHIP BETWEEN LECTURERS’ MOTIVATIONAL STRATEGIES AND STUDENTS’ SPEAKING ANXIETY AMONG VOCATIONAL COLLEGES STUDENTS IN SARAWAK - Rita Wong Chui Hung; Suyansah Swanto, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The investigation sought to explore the mediating role of Students’ Learning Styles (SLS) in the relationship between Lecturers’ Motivational Strategies (LMS) and Students’ Speaking Anxiety (SSA). A quantitative approach was utilized in the research through the distribution of self-administered questionnaires via a survey method to gather data from participants. A sample of 274 students from six Vocational Colleges in Sarawak for the academic year of 2021/2022 was selected using a simple random sampling technique. The research instruments included Lecturers’ Motivational Strategies derived from Dornyei and Cheng’s (2007) Taiwanese research, Grasha-Riechmaan's (1996) Students’ Learning Styles, and Students’ Speaking Anxiety adapted from Horwitz et al.'s (1986) Foreign Language Classroom Anxiety Scale (FLCAS). Data analysis was conducted using IBM-SPSS version 25.0 and IBM-SPSS-AMOS version 24.0 on the information collected from the field study to test the mediating effects of SLS. The results revealed that SLS mediated the relationship between LMS and SSA. Through the findings of this study, it had implied that by relying on motivational teaching strategies to address students' speaking anxiety in ESL classrooms might not be sufficient without taking into account their different learning styles. The implications of the research proposed that English lecturers in Vocational Colleges in Malaysia need to also recognize the diverse learning styles of students while undertaking the MPU 2222 English for Communication course in English as a Second Language (ESL) classrooms. The contemporary era has witnessed a transition in educational practices from the traditional teacher-centered approach to more student-centered methodologies, underscoring the importance of innovative teaching techniques that cater to the diverse needs of learners. Consequently, a profound comprehension of students' learning styles is imperative for educators, particularly language educators, in order to aptly select suitable teaching approaches.